The Effect of Modernization on Moral Degradation in the Independent Curriculum at Elementary Schools - Chaeroh, Miratu (UNDIKMA, 2024)
Modernization is a change that occurs in a multidimensional society in the social, political, economic, and cultural fields by utilizing technology and communication to achieve a better life. Moral degradation is a form of weakening a cultural value owned by society that leads to the formation of a new culture clash. Moral degradation is a form of weakening a cultural value owned by society that leads to the formation of a new culture clash. The purpose of this study is to determine the impact of modernization development on moral degradation, especially manners in elementary school students. The method used is Systematic Literature Review (SLR) which refers to a particular research methodology to collect data in accordance with the focus of the research topic. The development of modernization not only has a positive impact but also a negative impact that has an impact on moral decline, especially on manners in children. Modernization provides freedom and ease of access to information that has an impact on the lives of elementary school students prone to moral degradation. The results of this study students were able to limit themselves to the development of modernization through understanding the importance of social values and apply in the school environment. The impact of this study students can distinguish and select any modernization that has an impact on moral change